Structural design for the stage - Holden, Alys (Alys Elaine), 1971- (Focal Press/Taylor & Francis Group, 2015)
"The follow-up to the 2000 Golden Pen Award-winning Structural Design for the Stage, this second edition provides the theater technician with a foundation in structural design, allowing an intuitive understanding of "why sets stand up." It introduces the basics of statics and the study of the strength of materials as they apply to typical scenery, emphasizing conservative approaches to real world examples. This is an invaluable reference for any serious theatre technician throughout their career, from the initial study of the fundamental concepts, to the day-to-day use of the techniques and reference materials.Now in hardcover, with nearly 200 new pages of content, it has been completely revised and updated to reflect the latest recommended practices of the lumber and steel industries, while also including aluminum design for the first time. "--